Issues and Strategies for Accelerating the Implementation of Sustainable Smallholder Oil Palm Rejuvenation Program in Indonesia - Eka Sintha, Tri Yuliana; Pordamantra, Pordamantra; Prajawahyudo, Tri; Dewi Nopembereni, Eti; AD, Yuprin; Karuniawan Putera Asiaka, Fandi; Barbara, Betrixia; Ludang, Ellydia (Riviera Publishing, 2023)
This research aims to analyze various literature that discusses problems and strategies for accelerating the realization of the national sustainable smallholder oil palm rejuvenation (PSR) program. The primary method used in this research is a literature study (desk study). The results of the study show that there are several strategies that the government must implement to accelerate the realization of the sustainable PSR program in Indonesia. The strategies in question include mandatory ISPO certification in 2025 (Indonesian Sustainable Palm Oil) for smallholder oil palm plantations, increasing the resource capacity of smallholder oil palm growers in implementing good agricultural practices (GAPs), providing access to smallholder oil palm growers to production inputs, resolving legality issues. Smallholders' land, encouraging land productivity and strengthening smallholders in fulfilling ISPO certification requirements, strengthening the institution of smallholders as a forum for smallholders to access government programs, and encouraging entry into the palm oil (CPO) processing sector which is an industrial raw material, and the government and related parties signed PSR cooperation through partnerships.